2018
DOI: 10.1149/2.0841807jes
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering and Electrochemical Investigations on the Adsorption of Imidazole: Imidazolium Couple and Its Implications on Copper Corrosion Inhibition

Abstract: The adsorption dynamics of Imidazol (Imid) and Imidazolium (ImidH + ) on copper was investigated by Surface-Enhanced Raman Scattering (SERS) as a function of the applied potential and pH. Although both species adsorb on metal surfaces the neutral molecule changes the orientation from tilted to perpendicular as the potential is made more negative. On the other hand, the cation remains parallel over the whole studied potential window. Imid is the major species on copper electrode, although ImidH + can be identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…At E = −0.4 V, the overlapped bands at 625 and 530 cm −1 besides the 410 cm −1 one correspond to Cu 2 O, which is formed at a less cathodic potential due to the presence of atmosphere air. The 276 cm −1 band is typically assigned to the ν Cu‐Cl vibration and its appearance is fully justified by the chloride medium . The region characteristic of the ν C4C5 vibration shows a band at 1,560 cm −1 , but a closer look allows us identifying again the 1,599 cm −1 band, whose intensity is even smaller as compared with the spectrum at E = −1.0 V (Figure c).…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…At E = −0.4 V, the overlapped bands at 625 and 530 cm −1 besides the 410 cm −1 one correspond to Cu 2 O, which is formed at a less cathodic potential due to the presence of atmosphere air. The 276 cm −1 band is typically assigned to the ν Cu‐Cl vibration and its appearance is fully justified by the chloride medium . The region characteristic of the ν C4C5 vibration shows a band at 1,560 cm −1 , but a closer look allows us identifying again the 1,599 cm −1 band, whose intensity is even smaller as compared with the spectrum at E = −1.0 V (Figure c).…”
Section: Resultsmentioning
confidence: 76%
“…We have recently reported that Imid cannot be considered an efficient inhibitor at its natural pH (around 8.0) because it physically adsorbs on the oxidized copper surface at the corrosion potential and further reacts with corrosion products providing a soluble complex, in contrast to benzotriazole behavior in which an insoluble passive film is formed . Furthermore, our SERS data clearly show that imidazolium (ImidH + ) is the major species in extremely acidic medium (pH = 2.0) and near the corrosion potential, but its interaction to the metal surface is even weaker as compared with the neutral species.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations